2003
DOI: 10.1177/15648265030243s101
|View full text |Cite
|
Sign up to set email alerts
|

Introduction to the Proceedings of the International Research on Infant Supplementation (Iris) Initiative

Abstract: In 2001, students and professionals from 13 nations were hosted by UNICEF for the International Workshop on Multi-Micronutrient Deficiency Control in the Life Cycle in Lima, Peru, May 30-June 1, 2001. Workshop participants engaged in both narrow and broad discussions of ways to combat multiple micronutrient deficiencies in developing countries. Preliminary data from four common-protocol studies conducted in Peru, South Africa, Indonesia, and Vietnam were presented. Participants also discussed the immediate, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…We conclude that RUTF is an important advance in the management of severe malnutrition, so needs to be incorporated into treatment protocols. There are likely to be a new generation of diets for young children that present as spreads (FOODlet) 40–42 . However, such foods still suffer from the well‐known limitations of food supplement handouts, namely high cost, sharing with other family members (‘leakage’), compensatory reductions in home feeds (‘substitution’) and poor compliance (‘wastage’).…”
Section: What Is the Best Diet For Severe Malnutrition?mentioning
confidence: 99%
See 1 more Smart Citation
“…We conclude that RUTF is an important advance in the management of severe malnutrition, so needs to be incorporated into treatment protocols. There are likely to be a new generation of diets for young children that present as spreads (FOODlet) 40–42 . However, such foods still suffer from the well‐known limitations of food supplement handouts, namely high cost, sharing with other family members (‘leakage’), compensatory reductions in home feeds (‘substitution’) and poor compliance (‘wastage’).…”
Section: What Is the Best Diet For Severe Malnutrition?mentioning
confidence: 99%
“…There are likely to be a new generation of diets for young children that present as spreads (FOODlet). [40][41][42] However, such foods still suffer from the well-known limitations of food supplement handouts, namely high cost, sharing with other family members ('leakage'), compensatory reductions in home feeds ('substitution') and poor compliance ('wastage'). This problem was documented in a periodic 24-h dietary recall study that found index children received only 30% and 43%, respectively, of the provided supplement.…”
Section: High-energy Milk Dietsmentioning
confidence: 99%